Polarization-dominated thermal-electric-mechanical behaviours in GaN ceramics - Qin, G.S.; Zhou, X.P.; Wang, Y.; Lu, Chunsheng; Zhao, M.H. (2022)
In this paper, we have systematically investigated the polarization-dependent thermal-electric-mechanical behaviours in GaN piezoelectric semiconductor ceramics (PSCs). A thermo-piezoelectric semiconductor model is proposed with pyroelectric and thermoelastic as well as piezoelectric couplings. It is shown that polarization has a non-negligible influence on the thermoelectric properties of GaN ceramics. Because the potential barrier caused by pyroelectricity near the hot end suppresses the Seebeck effect, the thermoelectric potential and current of polarized samples obviously decrease with temperature difference. Moreover, it is the intercoupling between pyroelectric polarization and piezoelectric charges that largely affects the bending strength of GaN ceramics. Compared with the ordinary ceramics, the electromechanical and thermoelectric properties of GaN PSCs can be dominated through polarization.